2022
DOI: 10.3389/fimmu.2022.870283
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Immune Checkpoint Receptors and Ligands as Prognostic Biomarkers in COVID-19 Patients

Abstract: Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2. During T-cell activation, the immune system uses different checkpoint pathways to maintain co-inhibitory and co-stimulatory signals. In COVID-19, expression of immune checkpoints (ICs) is one of the most important manifestations, in addition to lymphopenia and inflammatory cytokines, contributing to worse clinical outcomes. There is a controversy whether upregulation of ICs in COVID-19 patients might lead to T-cell exhaustion or activation. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 158 publications
(237 reference statements)
0
19
0
Order By: Relevance
“…Since the COVID-19 vaccine was not available for most of the pandemic period in this study, it is possible that there was a differential impact of COVID-19 infection on tumors expressing high vs. low PD-L1 during pembrolizumab monotherapy. Moreover, during SARS-CoV-2 infection, investigators have described an upregulation of important immune checkpoint receptors and ligands such as PD-1, CTLA-4, TIM-3, LAG-3, and TIGIT [ 22 ]. The immune stimulatory effect due to SARS-CoV-2 infection may have been most beneficial among patients with tumors expressing lower PD-L1 undergoing pembrolizumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID-19 vaccine was not available for most of the pandemic period in this study, it is possible that there was a differential impact of COVID-19 infection on tumors expressing high vs. low PD-L1 during pembrolizumab monotherapy. Moreover, during SARS-CoV-2 infection, investigators have described an upregulation of important immune checkpoint receptors and ligands such as PD-1, CTLA-4, TIM-3, LAG-3, and TIGIT [ 22 ]. The immune stimulatory effect due to SARS-CoV-2 infection may have been most beneficial among patients with tumors expressing lower PD-L1 undergoing pembrolizumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients being treated with checkpoint blockade (or PD-L1 axis blockade) can develop decreased SARS-CoV-2 antibody titers after vaccination resulting in the CDC recommendation for a third booster in this population [ 24 ]. Furthermore, studies have shown that several co-inhibitory molecules (PD-L1, CTLA-4, TIM-3, LAG3, VISTA, TIGIT) are upregulated on T cells in patient with COVID-19 infections, and this might negatively interfere with antitumor immune responses induced by checkpoint inhibitors [ 25 , 26 ]. One study has suggested that while PD-1 expressing CD8 + T cells from COVID-19 patients are still functional, these T cells become exhausted [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the interaction between responded immune cells in the alveoli remains unclear. Early studies found that upregulation of inhibitory immune checkpoints (ICs) in COVID-19 is linked to exhaustion of T cells and NK cells [8]. The exhaustion of CD8 + T cells is evident in mild/moderate infections but it seems to be lower in severe infections that showed an increase in the cytokine-producing T cells [8].…”
Section: Introductionmentioning
confidence: 99%